GESTIÓN ESTRATÉGICA E INNOVACIÓN EN LAS PYMES PERUANAS BAJO EL ACTUAL CONTEXTO DE CRISIS ECONÓMICA INTERNACIONAL - Bouby Tolentino, Francisca (2013)
This paper wants to highlight the meaning for small Peruvian enterprises , in terms of management and innovation, to face a high level of competition in an open economy; but having as a framework the current international financial crisis which began in 2008 but seems not to be over. This only reaffirms cyclical capitalism trend, and also the big power of current financial system and a high competition that affects the competitiveness of any economy. With great impacts on developed and non developed economies , mainly inside Peruvian economy where it began to detect its initial effects.